2008
DOI: 10.2500/ajr.2008.22.3203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Weight Reduction on Rhinometric Measurements in Overweight Patients with Obstructive Sleep Apnea

Abstract: Weight reduction does not seem to have any effect on nasal resistance or volume in overweight patients with mild OSA. Patients with OSA and impaired nasal breathing need specific medical or surgical treatment to restore nasal airflow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 20 publications
0
27
0
1
Order By: Relevance
“…The WMD for AHI was −16.09 (95% CI −25.64, −6.54); however, this sample was again highly heterogeneous (I 2 = 92.2%). Sensitivity analysis was conducted to determine if outcomes differed when using the 12-week data [27], rather than the 12-month data of the study with different time points [31]. This analysis showed similar results (WMD = −15.76 (95% CI −26.45, −5.06), I 2 = 92.7%).…”
Section: Apnoea-hypopnoea Indexmentioning
confidence: 88%
See 3 more Smart Citations
“…The WMD for AHI was −16.09 (95% CI −25.64, −6.54); however, this sample was again highly heterogeneous (I 2 = 92.2%). Sensitivity analysis was conducted to determine if outcomes differed when using the 12-week data [27], rather than the 12-month data of the study with different time points [31]. This analysis showed similar results (WMD = −15.76 (95% CI −26.45, −5.06), I 2 = 92.7%).…”
Section: Apnoea-hypopnoea Indexmentioning
confidence: 88%
“…Follow-up data were reported for three of the RCTs. Specifically, follow-up data from Kemppainen et al [27] and Tuomilehto et al [31] were reported at 24 and 60 months [32,33]; follow-up data from Foster [24] were reported at 24 and 48 months [28]; and follow-up data from Johansson et al [25] were reported at 12 months [26]. Overall, the eight RCTs included 618 participants.…”
Section: Included Studiesmentioning
confidence: 95%
See 2 more Smart Citations
“…Six randomised controlled trials have compared the effect of intensive lifestyle changes versus routine care in OSA [74][75][76][77][78][79]. The trials were mixed in duration, design and protocols employed, and no consistency was observed in the diet, exercise or structuring of the programmes employed (table 1).…”
Section: Osa and Liver Damagementioning
confidence: 99%